What Shapes Players' Performance in Soccer? Empirical Findings from a Panel Analysis - Benno Torgler; Sascha Schmidt (Center for Research in Economics, Management and the Arts (CREMA), 2006)
In this paper we investigate the pay-performance relationship of soccer players using individual data from eight seasons of the German soccer league Bundesliga. The results of our panel analysis show that not only the absolute income level, but also the relative income position affects players' performances. We also find the tendency of a non-linear effect. Finally, the paper investigates the performance impact of team effects. Our analysis provides evidence of a direct impact of teammates' attributes on individual player performance
Keywords: J31; J44; L83; 330; soccer; sport economics; performance; salary; positional concerns; team effects